2022
DOI: 10.3390/ijerph19095411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Health Literacy on Maintenance of Exclusive Breastfeeding at 6 Months Postpartum: A Multicentre Study

Abstract: Background: International organizations recommend initiating breastfeeding within the first hour of life and maintaining exclusive breastfeeding for the first 6 months. However, worldwide rates of exclusive breastfeeding for 6-month-old infants is far from meeting the goal proposed by the World Health Organization, which is to reach a minimum of 50% of infants. Education is one of the factors affecting the initiation and continuation of breastfeeding, and incidentally, it is also related to lower health litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
1
15
3
Order By: Relevance
“…We did not observe differences in the rates of EBF at 3 or 6 months of follow-up in either group, despite (at least in the rst telephone contact), there being a greater proportion of mothers who had had a COVID-19 infection at the time of the birth who had gone back to work and who reported a lower application of conditions aimed at facilitating the continuation of breastfeeding. Although it is true that the rates of EBF are higher than those described at three and six months in other studies conducted in our eld [47][48][49] , they do not reach the value determined by the WHO as one of their objectives for 2025 (rates of EBF at 6 months of at least 50%) 50 . With regard to the impact that the pandemic has had on the rates of EBF at 3 and 6 months, we noted how in the study conducted by Maria et al 29 on the newborns of mothers with a COVID-19 infection at the time of birth between March and June 2020, they obtained rates of EBF at 3 months of 16% vs. 93.5% in the newborns of those mothers without a COVID-19 infection; differences that were in uenced by the initial recommendation to separate the mother-infant pair and by the fear of transmitting the infection via breast milk.…”
Section: Discussioncontrasting
confidence: 64%
“…We did not observe differences in the rates of EBF at 3 or 6 months of follow-up in either group, despite (at least in the rst telephone contact), there being a greater proportion of mothers who had had a COVID-19 infection at the time of the birth who had gone back to work and who reported a lower application of conditions aimed at facilitating the continuation of breastfeeding. Although it is true that the rates of EBF are higher than those described at three and six months in other studies conducted in our eld [47][48][49] , they do not reach the value determined by the WHO as one of their objectives for 2025 (rates of EBF at 6 months of at least 50%) 50 . With regard to the impact that the pandemic has had on the rates of EBF at 3 and 6 months, we noted how in the study conducted by Maria et al 29 on the newborns of mothers with a COVID-19 infection at the time of birth between March and June 2020, they obtained rates of EBF at 3 months of 16% vs. 93.5% in the newborns of those mothers without a COVID-19 infection; differences that were in uenced by the initial recommendation to separate the mother-infant pair and by the fear of transmitting the infection via breast milk.…”
Section: Discussioncontrasting
confidence: 64%
“…However, metanalysis and systemic review have shown that a multifaceted approach of implementation during both the prenatal and postnatal periods increased the rate of EBF by 3.3 times at 6 months (Kim et al, 2018) and community outreach counseling (Kimani-Murage et al, 2017). However the higher level of education and in particular maternal health literacy level was shown to significantly increase EBF to 6 months (Valero-Chillerón et al, 2022). Maternal health literacy is defined as the acquisition of required cognitive and social skills to enable women to access, understand, appraise, and use the information needed to maintain and enhance their health conditions (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… Valero-Chillerón et al (2022). also found that health literacy levels were closely related to maintaining exclusive breastfeeding and play a protective role against early cessation.…”
mentioning
confidence: 91%